Purulent-Inflammatory Diseases of the Maxillofacial Region in Patients with Various Chronic Diseases - Mahmudov Jahongirmirzo Komilovich (Universitas Muhammadiyah Sidoarjo, 2022)
In the practice of doctors of all specialties the proportion of patients suffering from combined diseases (polymorbide states) is steadily increasing. The sphere of dentistry and maxillofacial surgery is not an exception. The paper considers the main etiopathogenetic mechanisms in the combination of purulentinflammatory diseases of the maxillofacial region (PID MFR) with somatic pathology (synthropy). Data on the features of the combination of somatic diseases with PID MFR, the role of chronic stress, immunopathies, medico-social factors in the development of pathological processes in the oral cavity and surrounding tissues are summarized. The features of the course of PID MFR in the elderly and elderly patients with polymorbid conditions are shown; persons suffering from drug addiction and alcoholism with visceropathy. The analysis of approaches to the evaluation of the severity of PID MFR and their treatment is carried out. It is emphasized that in the clinic of maxillofacial surgery it is necessary to study complex somatic and mental pathology in a complex way (multidisciplinary principle) and to take into account the results in developing the tactics of patient management. Integral approach will fully realize the principle of personification of medical care.